Studi Literatur: Peran Bahan Ajar Berbasis Realistic Mathematics Education Pada Pembelajaran Matematika Siswa SMP - Tika Kurnia Amaliyah; Silvira Hakim; Meiliasari; Pinta Deniyanti Sampoerno (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2021)
This research is a qualitative type of research conducted using literature study method. The purpose of this research is to describe the role of Realistic Mathematics Education (RME) based teaching materials on the mathematics learning of junior high school students. In this research, articles were used as literature which were obtained through the search using relevant key words and through screening process using certain criteria until finally obtained 10 articles, with details of 7 articles from nationally accredited journal Sinta and 3 articles from international journal accredited Scopus, where all the articles discuss about Realistic Mathematics Education (RME) based teaching materials and the influence of their use (effectiveness of their use on mathematical learning) received by students. Those articles were then analysed using content analysis technique. Based on this study, it was obtained that Realistic Mathematics Education (RME) based teaching materials play role in terms of spatial ability, problem solving, reasoning, creative thinking, mathematical communication, mathematical literacy, mathematical representation, as well as motivation, self-efficacy, and learning independence of junior high school students. Authors recommend that the further research regarding the similar topic should be done for other education level, such as elementary school or senior high school.